2012
DOI: 10.1115/1.4006426
|View full text |Cite
|
Sign up to set email alerts
|

Stall Warning by Blade Pressure Signature Analysis

Abstract: At low mass flow rates, axial compressors suffer from flow instabilities leading to stall and surge. The inception process of these instabilities has been widely researched in the past---primarily with the aim of predicting or averting stall onset. In recent times, attention has shifted to conditions well before stall and has focused on the level of irregularity in the blade passing signature in the rotor tip region. In general, the irregularity increases in intensity as the flow rate through the compressor is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…Other authors, for example, Wisler et al [15], connect the occurrence of RI in Mailach et al to the fact that one stage of the four-stage compressor has been weakened by a tip clearance increase. Young et al [16], however, found similar disturbances as Mailach et al and März et al that rotated relative to the rotor under near stall conditions in their investigated single-stage compressor with large tip clearance. According to Camp and Day [17] compressor stall can be caused by a local (mostly in the rotor tip) flow breakdown, the so called spikes, in only one or two blade passages that grow into stall cells.…”
Section: Introductionmentioning
confidence: 57%
“…Other authors, for example, Wisler et al [15], connect the occurrence of RI in Mailach et al to the fact that one stage of the four-stage compressor has been weakened by a tip clearance increase. Young et al [16], however, found similar disturbances as Mailach et al and März et al that rotated relative to the rotor under near stall conditions in their investigated single-stage compressor with large tip clearance. According to Camp and Day [17] compressor stall can be caused by a local (mostly in the rotor tip) flow breakdown, the so called spikes, in only one or two blade passages that grow into stall cells.…”
Section: Introductionmentioning
confidence: 57%
“…After repeating this process for 100 revolutions, the mean of all RMS was nondimensionalised by the dynamic pressure at the rotor inlet. A detailed description of the presented analysis procedure is given by Young et al (2011) [5]. It is now possible to determine the variance of pressure fluctuations caused by the disturbances themselves.…”
Section: Prestall Disturbancesmentioning
confidence: 99%
“…However, unsteadiness increased uniformly over the entire frequency domain at N = 70% and N = 80%. Young et al [29] suggested that non-uniform tip clearance was the main cause of the pressure irregularity on the basis of the experimental results in a low-speed compressor. However, the reason for the increase in the pressure signal irregularity at the rotor tip is not yet understood clearly.…”
Section: Irregularity Of Rotor Tip Pressurementioning
confidence: 98%